The case of the prowling bear [compact disc, unabridged] - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2013)
Everyone knows that bears live in the mountains and there are no mountains in the Texas Panhandle. So, when Slim claims to have seen a bear cross the road, no one knows what to believe, that is, until Deputy Kile spreads a report that there really is a bear on the loose in Ochiltree County! With news like this, the ranch's Security Force goes on Red Alert. Will Hank be able to defend the ranch from a raging, prowling bear?